Flow cytometry for biotechnology - Sklar, Larry A. (Oxford University Press, 2005)
Shows how flow cytometry is integrated into modern biotechnology. This volume deals with issues of content, sensitivity, and high throughput informatics with applications in genomics, proteomics and protein-protein interactions, drug discovery, vaccine development, plant and reproductive biology, pharmacology and toxicology, and more.